2022
DOI: 10.1155/2022/8006642
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Fucoidan-Chitosan Nanoparticles Targeting P-Selectin for Effective Atherosclerosis Therapy

Abstract: Atherosclerosis is the key pathogenesis of cardiovascular diseases; oxidative stress, which is induced by the generated excess reactive oxygen species (ROS), has been a crucial mechanism underlying this pathology. Nanoparticles (NPs) represent a novel strategy for the development of potential therapies against atherosclerosis, and multifunctional NPs possessing antioxidative capacities hold promise for amelioration of vascular injury caused by ROS and for evading off-target effects; materials that are currentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 104 publications
0
3
0
Order By: Relevance
“…In this experiment, CFNs effectively scavenged hydroxyl radicals and superoxide radicals and inhibited the secretion of inflammatory factors IL-6, IL-1β, and TNF-α in macrophages. A large accumulation of green CFNs in atherosclerotic plaques was observed by fluorescence imaging, confirming their good targeting ability [ 57 ].…”
Section: Ros Scavenging and Modulating Strategies Based On Npsmentioning
confidence: 88%
“…In this experiment, CFNs effectively scavenged hydroxyl radicals and superoxide radicals and inhibited the secretion of inflammatory factors IL-6, IL-1β, and TNF-α in macrophages. A large accumulation of green CFNs in atherosclerotic plaques was observed by fluorescence imaging, confirming their good targeting ability [ 57 ].…”
Section: Ros Scavenging and Modulating Strategies Based On Npsmentioning
confidence: 88%
“…Furthermore, CFNs intravenously injected into atherosclerotic ApoE −/− mice accumulated in atherosclerotic plaques, subsequently decreasing the average plaque area (by 36.5%), and the necrotic core area, and enhancing the fibrous cap thickness around the plaques, thus stabilising the atherosclerotic plaques. At the same time, long-term CFN treatment did not cause any significant adverse effects on the heart, liver, lungs, spleen, or kidneys, thus confirming its safety [ 33 ]. Together, the in vitro and in vivo results suggested that COS effectively reduced lipid levels, and suppressed local oxidative stress and inflammation, by targeting P-selectin in atheromatous plaques, and modulating the lipid metabolism, thereby preventing the progression of atherosclerosis.…”
Section: Chitosan Oligosaccharidementioning
confidence: 91%
“…This modification enabled the NPs to effectively impede leukocyte recruitment and rolling on platelets and endothelium. These NPs were shown to exhibit antioxidant and anti-inflammatory properties in vitro and effectively suppressed local oxidative stress and inflammation in mice [185]. Tempol (SOD mimetic agent) and phenylboronic acid pinacol ester (a hydrogen peroxide-eliminating compound) were encapsulated onto a cyclic polysaccharide β-cyclodextrin NPs.…”
Section: Cardiovascular Diseasesmentioning
confidence: 99%